Natural Disaster Management in Local Government from the Perspective of Collaborative Governance - Wahyuli, Sri; Nurfarhaty, Nurfarhaty; Haeril, Haeril (Department of Government Studies, Universitas Muhammadiyah Buton., 2023)
This research aims to evaluate the collaborative governance approach in the pre-disaster phase and the efforts made by various actors to anticipate disasters in Bima Regency. The research used a descriptive qualitative method with subjects selected through a purposive sampling technique. Data collection techniques included observation, interviews, and documentation. The research results indicate that disaster management in Bima Regency is conducted through a collaborative governance approach involving all elements of society. The Disaster Management Agency (BPBD) acts as the leading sector in implementing programs in the Regional Disaster Management Plan in collaboration with cross-sectoral partners. This collaboration process has also integrated the Disaster Management Plan into the strategic and annual work plans of all SKPDs, and the local government collaborates with universities in developing research results that can be directly applied by the government, individuals, and families. This collaboration has resulted in disaster mitigation strategies focused on strengthening the legal framework, increasing capacity, and accountability of disaster management governance.